DIASTOLIC DYSFUNCTION AND REMODELING OF THE LEFT VENTRICULAR DEPENDING ON THE CONTROL OF GLYCEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - A. E. Kratnov; E. V. Koroleva (Евразийский Кардиологический Журнал)
The aim. Studying of influence of the control glycaemia on development of diastolic dysfunction and remodelling of left ventricular in patients with type 2 diabetes mellitus (DM) with presence or absence of essential arterial hypertension was evaluated. Material and methods. In 133 patients with DM aged 26 to 66 years without ischemic heart disease the echocardiography with estimation of diastolic properties and diagnostics of remodeling of left ventricular has been investigated. Results. The diastolic dysfunction in 25.9% and remodeling of left ventricular in 35.4% patients with DM without essential arterial hypertension were observed. Poor compensation of DM (level of HbAlc >7,5 %), which was accompanied by more often development of demyelinating neuropathy, resulted in weighting of diastolic dysfunction and remodelling of left ventricular as with presence, and absence of the essential arterial hypertension in patients with diabetes. Conclusion. Absence of indemnification of exchange of the carbohydrates in patients with MD irrespective of presence of arterial hypertension associates with more expressed remodelling of the hearts.